Motives and Preferences for Participation in Outdoor Recreation Among Members of Selected Youth Recreation Associations: An Exploratory Study - Lee, Kwan Meng (2003)
Outdoor recreation activities are popular among most Malaysian youths. It is also being used to develop their personalities and competencies. Since recreation participation is voluntary, the youths must be motivated to participate. Their motivation is influenced by their behavioural patterns such as preferences and needs. The study was carried out to determine the pattern of their motives and preferences, and the profile of youths from selected youth recreation associations who participated in such activities, as well as to determine the variables that influenced their participation Descriptive research design using self-administered questionnaire was adopted for this study. The purposive sample population came from members of selected youth recreation NGOs and youth NGOs, local institutions and other recreation programmes. The respondents of the study reside in the Klang Valley. They comprised both the males and females, belong to youth with age groups of 15 to 25 years and 26 to 40 years. In addition, the respondents are mainly students from non-tertiary and tertiary institutions, as well as youths who are employed in both public and private sectors. The findings suggest that health and fitness, self-confidence, peace, developing skills, and nature appreciation are the top five predominant preferred motives for their participation in their personal development. The respondents regardless of their socio-economic background prefer to participate in outdoor recreation activities on weekends or a period of not more than 5 days, social participation with their friends and peers in pursuing recreation and through their association, or institutions which they belong to. They prefer to travel to destinations close to their homes of within 20 kilometres for their recreation using a combination of transportation means. Learning safety, camping and exploration skills are their main preferred training need. They prefer quality managers and good leaders for their activity delivery. Camping, swimming and flying are the most preferred activities. However, the main constraints to their participation are money, time, transport, equipment, companionship and lack of information about recreation programmes.